2009
DOI: 10.1177/0960327109346789
|View full text |Cite
|
Sign up to set email alerts
|

Safety of a novel galacto-oligosaccharide: Genotoxicity and repeated oral dose studies

Abstract: A series of safety tests were undertaken on a novel galacto-oligosaccharide (GOS) produced from lactose by a two-step enzymatic process involving Sporobolomyces singularis and Kluyveromyces lactis. Bacterial reverse mutation and chromosomal aberration tests, with or without metabolic activation, were performed. These tests showed no mutagenesis in the Ames assay or in Escherichia coli WP2uvrA, and no chromosomal aberrations in cultured fibroblast cells from Chinese hamster lungs (CHL/IU). Micronuclei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 24 publications
0
24
1
Order By: Relevance
“…The GOS was a commercial product of Oligomate (Yakult, Tokyo, Japan) and was prepared with Kobayashi et al . 's () method.…”
Section: Methodsmentioning
confidence: 58%
See 1 more Smart Citation
“…The GOS was a commercial product of Oligomate (Yakult, Tokyo, Japan) and was prepared with Kobayashi et al . 's () method.…”
Section: Methodsmentioning
confidence: 58%
“…The present study used galacto-oligosaccharide (GOS), a commercial product (Yakult, Tokyo, Japan), for its prebiotic testing (Kobayashi et al, 2009). Consuming GOS may relieve the symptoms of constipation (Nittynen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…24) With regard to the safety of GOS, general toxicity and genetic toxicity studies have raised no safety concerns. 25,26) GOS products supplied by three manufacturers were approved in the GRAS Notice Inventory of the US FDA (GRAS Notice Nos. GRN 236, 285 and 286, 334).…”
mentioning
confidence: 99%
“…In this study, Gossence™ (GOS) was found to be non-genotoxic in both Ames test and in vitro chromosomal aberration test with HPBL, which is consistent with published reports with similar class of compounds. 11 In vivo micronucleus test was negative with GOS at a doable maximum dose. 2 The results of the current study and published literature suggest that GOS do not have genotoxic potential.…”
Section: Discussionmentioning
confidence: 98%
“…GOS is mainly added to infant formula as it is able to stimulate growth of beneficial intestinal microflora such as bifidobacterium and reinforce microbiota similar to that of in breastfed infants. [11][12][13] Gossence™ is a GOS containing product manufactured by the action of enzymes from whole microbial cells (Sporobolomyces singularis MTCC5491) in a manner like other GOS products in the market. In this report, the safety of Gossence™ (GOS) was demonstrated by repeat dose oral toxicity study for 90-days followed by 28-day recovery period in Sprague Dawley rats and by assessing for its genotoxicity potential.…”
Section: Introductionmentioning
confidence: 99%